A cluster of rotavirus enteritis in pediatric liver recipients. Issue 3 (19th May 2015) - Cui, H.; Bai, S.; Huo, Z.; Li, J.; Sun, J.; An, X.
Abstract We observed a cluster of 4 pediatric liver recipients who developed diarrhea in a liver transplant unit within 5 days. Feces from these 4 patients were rotavirus positive when tested with Colloidal Gold Diagnostic Kit. Nucleic acid from 3 fecal specimens was extracted and reverse transcribed. Two were amplified positively. The complementary DNAs were sequenced. Alignment and phylogenetic analysis were performed with MEGA 6.06. Although involving only 4 pediatric liver recipients, this cluster was caused by at least 2 distinct G9P[8] rotavirus strains and included community infection and nosocomial infection.